Análise sensitiva do índice de qualidade de água IQACCME - Finazzi, Ana Elisa Martinelli (2012)
Assessment of water quality can be defined as the analysis of physical, chemical and biological characteristics of water. Water quality indices aim at giving a single value to the water quality of a source reducing great amount of water quality variables into a simpler expression and enabling easy interpretation of monitoring data. In this sense, the water quality index (WQI) used for assessing surface water quality are discussed. Although the standard WQINSF is one of the most widely used water quality indices, it also has some serious imitations. The index is employed to show, pollution caused by releases of industrial and domestic sewage but its practical outcomes are negatively affected by a series of monitoring constraints. Generally other then the nine core variables are monitored but not taken into account in rating the water quality. As outlined in the report of the National Water Agency (ANA) of Brazil, the index is not feasible to report the water quality at national level because the majority of variables are sampled only quarterly. Only twelve Brazilians states perform the WQINSF calculations and there are differences regarding the variable and method of calculation between the states. The WQICCME incorporates three elements: Scope - the number of water quality variables not meeting water quality objectives F1; Frequency - the number of times the objectives are not met F2; and Amplitude the extent to which the objectives are not met F3. In this context, we performed a sensitivity analysis to assess the applicability of the WQICCME for rating water quality of Brazilian rivers. The analysis was carried at three sampling station located at Cuiabá River representing different land usage to verify the influence of number of variables, sampling frequency and censored data in index classification. Regardless of the number of variables and observations used in the calculation of the index, if F1 (scope) is constant the classification remains constant. The censored data only play role in classification if the detection limit of the analytical method is out of the range of water quality objectives. Results suggest that WQICCME provides a way to resolve the non-uniformity of calculating the water quality and is a consistent procedure to report water quality to both management practitioners and the general public.